Implementation of Measurement of Zakat Village Index in Cibungur Village, Parungponteng District, Tasikmalaya Regency - M Silmi Mubarok; Mulia Amirullah; Eris Munandar (Jurnal Kewarganegaraan, 2022)
Abstract The Zakat Village Index is a mechanism tool used to measure the condition of a village so that it can be said that it is feasible or not feasible to be assisted by Baznas with zakat funds. Therefore, the Zakat Village Index can also be used as a monitoring and evaluation tool for the zakat management process in a village. The objectives of this study to be achieved include knowing the implementation of the Zakat Village Index for economic dimensions, health dimensions, and education dimensions for the people of Cibungur Village, Parungponteng District, Tasikmalaya Regency. social and humanitarian dimensions, and dimensions of da'wah or religion in the Cibungur Village community, Parungponteng District, Tasikmalaya Regency. This research uses mixed method research, which combines qualitative and quantitative methodologies to analyze a study. This method allows researchers to present studies qualitatively through descriptive explanations and also quantitatively through numbers, graphs, charts, and statistical data. Based on the research results, it can be concluded as follows: (1) The economic dimension index value has a value of 0.43. (2) The index value of the health dimension is 0.693. (3) The index value of the education dimension is 0.92 (4) The index value of the social and humanitarian dimension is 0.948 (5) The index value of the da'wah dimension is 1. Based on the measurement results of the Zakat Village Index (IDZ) obtained a value of 0.78. Categorized, Cibungur Village is included in the good category, which means that it is not prioritized for assistance. Keywords: Implementation, Measurement, IDZ